2015
DOI: 10.1177/0269216315616763
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of health professionals on subcutaneous hydration in palliative care: A qualitative study

Abstract: Variables which most often influence the use of subcutaneous route to hydration are those that are linked to the characteristics of the patient, the team and the family, and other like the context and professionals' subjective perceptions about this medical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(74 reference statements)
0
10
0
Order By: Relevance
“…With regard to perceived usefulness, despite some respondents claiming not to have guidelines, algorithms or protocols available, the results show that they consider them to be useful tools. In consonance with other authors, these tools are seen to facilitate decision‐making processes and diminish variability in clinical practice and ongoing training, with the main disadvantages being the lack of potential for personalising care plans (Beghi et al, ; Fischer et al, ; Gundersen, ; Woolf, Grol, Hutchinson, Eccles, & Grimshaw, ) and the perception of such interventions as a basic level of care given the symbolic value of hydration (Cabañero‐Martínez et al, ; Gent et al, ).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…With regard to perceived usefulness, despite some respondents claiming not to have guidelines, algorithms or protocols available, the results show that they consider them to be useful tools. In consonance with other authors, these tools are seen to facilitate decision‐making processes and diminish variability in clinical practice and ongoing training, with the main disadvantages being the lack of potential for personalising care plans (Beghi et al, ; Fischer et al, ; Gundersen, ; Woolf, Grol, Hutchinson, Eccles, & Grimshaw, ) and the perception of such interventions as a basic level of care given the symbolic value of hydration (Cabañero‐Martínez et al, ; Gent et al, ).…”
Section: Discussionmentioning
confidence: 82%
“…In consonance with other authors, these tools are seen to facilitate decision-making processes and diminish variability in clinical practice and ongoing training, with the main disadvantages being the lack of potential for personalising care plans (Beghi et al, 1998;Fischer et al, 2016;Gundersen, 2000;Woolf, Grol, Hutchinson, Eccles, & Grimshaw, 1999) and the perception of such interventions as a basic level of care given the symbolic value of hydration (Cabañero-Martínez et al, 2016;Gent et al, 2015). Considering this perspective, the results on the availability of and adherence to hydration guidelines and protocols could be explained, first, by the scarce and controversial evidence in favour of assisted hydration in patients with palliative needs and end-of-life situations (Forbat et al, 2017).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A small prospective study further explored SC hydration in palliative care, demonstrating that family caregivers and hospice nurses can administer SC hydration at end of life at home with minimal burden, equipment or technical support [65]. A qualitative review found that symptomatology was the most mentioned determinant of whether to hydrate or not, while the main criticisms were the potential side effects and difficulty in withdrawing hydration [66]. Findings from an RCT of significant efficacy, as well as efficiency, has led two authors to recommend its use in pediatric emergency departments [16,50].…”
Section: Discussionmentioning
confidence: 99%
“…Lack of training and organizational protocols and unawareness of the subcutaneous route for the administration of fluids is a barrier to use [50,66]. In the pediatric study of SC hydration, the lack of organizational protocols and staff awareness limited its usage and hence available outcome data.…”
Section: Discussionmentioning
confidence: 99%